Analysis of lipid oxidation (AOCS Press, 2005)
The book offers knowledge about anlytical methodology of lipid oxidation. Traditional analytical methods have been increasingly replaced by modern sophisticated instrumental methods, but lipid oxidation still presents a challenge in regard to its detailed mechanism, as well as its implications in the stability of biological tissues/compartments and "inter alias" human health.